ChemInform Abstract: Efficient Synthesis of Chiral Trisubstituted 1, 2‐Allenyl Ketones by Catalytic Asymmetric Conjugate Addition of Malonic Esters to Enynes. Issue 22 (12th May 2016) - Yao, Qian; Liao, Yuting; Lin, Lili; Lin, Xiaobin; Ji, Jie; Liu, Xiaohua; Feng, Xiaoming
Abstract: The conjugate addition of malonic esters to enynes in the presence of a scandium(III)/N, N‐dioxide complex yields a range of trisubstituted allenyl ketones with good diastereomeric ratios and excellent e.e.‐values.